THE EFFECT OF BRIDGE’S PIER HEIGHT TO THE BEHAVIOR OF GROUP BORED PILE FOUNDATION DUE TO PUSHOVER ANALYSIS - Basit Al Hanif (University Muhammadiyah Jakarta, 2023)
This study examines the behavior of pile foundations in relation to pier height as a result of pushover load analysis. The pier column was elevated in this investigation with fixed stiffness (EI) and by altering the EI value. A pushover analysis is performed on the bridge structure using the preset variables, and the behavior of the bored pile group foundation is examined owing to the pushover load. The bridge structure is analyzed using the Midas Civil Program, and the piling foundation response is analyzed using the FB-Multipier Program. By keeping the EI value constant at each height, the resulting pier pile base shear force diminishes with height. Meanwhile, by adjusting the EI stiffness value, the base shear force is kept roughly constant at each height. The fixed value of the EI stiffness has no effect on the depth of fixity. Meanwhile, varying the EI stiffness changes the pile foundation's depth of fixity.